2019
DOI: 10.1158/0008-5472.can-18-4044
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG10 Facilitates Hepatocarcinogenesis and Metastasis by Modulating Its Homolog SCARNA13 via a Positive Feedback Loop

Abstract: Understanding the roles of noncoding RNAs (ncRNA) in tumorigenesis and metastasis would establish novel avenues to identify diagnostic and therapeutic targets. Here, we aimed to identify hepatocellular carcinoma (HCC)-specific ncRNA and to investigate their roles in hepatocarcinogenesis and metastasis. RNA-seq of xenografts generated by lung metastasis identified long noncoding RNA small nucleolar RNA host gene 10 (SNHG10) and its homolog SCARNA13 as novel drivers for the development and metastasis of HCC. SNH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 34 publications
7
104
0
Order By: Relevance
“…We noticed that the in vivo effects are more pronounced than the in vitro effects in bladder cancer. Several studies (35)(36)(37)(38) have shown a similar pattern. One of the possible reasons is that we used transient transfected bladder cancer cells for in vitro assays, whereas steady transfected bladder cancer cells were used for in vivo experiments.…”
Section: Discussionsupporting
confidence: 55%
“…We noticed that the in vivo effects are more pronounced than the in vitro effects in bladder cancer. Several studies (35)(36)(37)(38) have shown a similar pattern. One of the possible reasons is that we used transient transfected bladder cancer cells for in vitro assays, whereas steady transfected bladder cancer cells were used for in vivo experiments.…”
Section: Discussionsupporting
confidence: 55%
“…LncRNAs have been reported to participate in the progression of various types of tumors, including lung cancer . For example, Yu et al .…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA H19 decreases the transcriptional activity of p53 [30]. LncRNA SNHG10 facilitates hepatocarcinogenesis and metastasis by modulating its homolog Small Cajal body-specific RNA 13 (SCARNA13) [31]. LncRNAs can also achieve the regulation of the expression of the target genes by recruiting some RNA-binding proteins [32].…”
Section: Introductionmentioning
confidence: 99%